Analysis of The Effect of Price Perception and Service Quality on Customer Loyalty with Customer Satisfaction as A Mediating Variable - Wihalauw, Margaretta Wellia; Yulianti, Ida (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The currently proliferating modern lifestyle of practicality and efficiency among Indonesians has boosted the growth of laundry industry in the country. One of the players in this industry is Bibi Coin Laundry, a laundromat business established in 2019 in Tangerang. Despite its stable operation, fierce competitions have urged this company to work on the loyalty of its customer. This quantitative study aims to analyze the impacts of price perception and service quality on customer loyalty with the mediation of customer satisfaction. The data was harvested via questionnaires distributed to the company’s customers and analyzed using Structural Equation Modeling approach. The results of the hypothesis testing indicate that price perception positively and insignificantly influences customer loyalty with the coefficient of 0.394 at 0.7 significance. Then, service quality positively and significantly affects customer loyalty with the coefficient of 0.678 at 0.003 significance, and customer satisfaction partially mediates the effects of price perception and service quality on customer loyalty with the significance value of P<0,05. Based on these findings, Bibi Coin Laundry is suggested to consider the use of a competitive price strategy and to enhance its service quality